Evaluation of antioxidant and fibrinolytic activities of hot aqueous extracts of Pleurotus pulmonarius (FRIES) quélet hybrids / Ummu Humaira Hassan - Ummu Humaira, Hassan (2017)
In Malaysia, there is a high market demand for oyster mushroom due to its nutritional value, therapeutic properties and biotechnological applications. Pleurotus pulmonarius commonly known as grey oyster mushroom is one of the most popular mushroom and has gained demand worldwide. Studies have demonstrated that regular consumption of P. pulmonarius in human diet may be beneficial for health and act as protective agents to help the human body reduce oxidative damage. Due to high nutritional value and fast growing nature, P. pulmonarius hybrid was introduced to produce high quality mushrooms. Besides, P. pulmonarius has been used more as a food than as medicinal purpose. Therefore, in this study, antioxidant activity of the P. pulmonarius was evaluated to compare antioxidant activity of the hybrids (UMH001, UMH002 and UMH004) and the parents (UMP001, UMP002 and UMP003). Hot aqueous extracts were prepared to mimics cooking methods. This is typical way how edible mushrooms are consumed. Four different antioxidant assays were carried out viz., DPPH free scavenging activity, ferric reducing antioxidant power, inhibition of lipid peroxidation of buffered egg yolk and Trolox Equivalent Antioxidant Activity (TEAC) assay. The total phenolic content was determined by Folin-Ciocalteu reagent by using gallic acid for comparison. The hybrid UMH001 exhibited significant (P<0.05) scavenging activity (IC50 of 11.86 ± 0.42mg/ml), followed by UMH004 and UMH002 having IC50 15.84 ± 0.41 and 16.04 ± 3.81 mg/ml, respectively. The weakest scavenging activity with an IC50 of 26.35 ± 2.30mg/ml was recorded in the parent UMP002. On the other hand, UMH001 had 32% higher ability to inhibit lipid peroxidation (IC50 of 29.57 ± 0.89mg/ml) compared to other mushroom extracts. All the hybrids showed lower ferric reducing power (absorbance ranging from 0.120-0.144) when compared to parents (absorbance 0.132-0.162) at 1.0 mg/ml. Further, UMP003 showed higher TEAC value (70.41 μmol TE/100 g dry weight) when compared to the other hybrid and parent extracts. The hybrids of P. pulmonarius lost their quality compared to parents. However, there was no correlation between total phenolic content and antioxidant activities. There could be other bioactive compounds such as flavonoid, ascorbic acid and tocopherol present in the mushroom extracts. In addition, antioxidant potential of each mushroom was calculated based on the average percentage relative to butylated hydroxyanisole (BHA) and summarised as antioxidant index (AI). UMP002 (7.68%), UMH004 (6.85%) and UMP001 (6.38%) showed relatively high AI. Meanwhile, all the extracts tested were not cytotoxic to RAW264.7 cells. All the mushroom extracts also showed no fibrinolytic activity in fibrin plate assay. The enzyme might be denatured during the extract preparation by using hot aqueous to mimic the typical way how edible mushrooms are prepared for consumption. In conclusion, UMP002 exhibited significantly (P<0.05) higher antioxidant activities and could serve as a natural antioxidant. There was no significant difference (p˃0.05) in antioxidant activity between the hybrids and parent of UMP002.